Bimetallic Metal‐Organic Frameworks: Probing the Lewis Acid Site for CO2 Conversion. Issue 17 (22nd February 2016) - Zou, Ruyi; Li, Pei‐Zhou; Zeng, Yong‐Fei; Liu, Jia; Zhao, Ruo; Duan, Hui; Luo, Zhong; Wang, Jin‐Gui; Zou, Ruqiang; Zhao, Yanli
Abstract : A highly porous metal‐organic framework (MOF) incorporating two kinds of second building units (SBUs), i.e., dimeric paddlewheel (Zn2 (COO)4 ) and tetrameric (Zn4 (O)(CO2 )6 ), is successfully assembled by the reaction of a tricarboxylate ligand with Zn II ion. Subsequently, single‐crystal‐to‐single‐crystal metal cation exchange using the constructed MOF is investigated, and the results show that Cu II and Co II ions can selectively be introduced into the MOF without compromising the crystallinity of the pristine framework. This metal cation‐exchangeable MOF provides a useful platform for studying the metal effect on both gas adsorption and catalytic activity of the resulted MOFs. While the gas adsorption experiments reveal that Cu II and Co II exchanged samples exhibit comparable CO2 adsorption capability to the pristine Zn II ‐based MOF under the same conditions, catalytic investigations for the cycloaddition reaction of CO2 with epoxides into related carbonates demonstrate that Zn II ‐based MOF affords the highest catalytic activity as compared with Cu II and Co II exchanged ones. Molecular dynamic simulations are carried out to further confirm the catalytic performance of these constructed MOFs on chemical fixation of CO2 to carbonates. This research sheds light on how metal exchange can influence intrinsic properties of MOFs. Abstract : A cation‐exchangeable metal‐organic framework (MOF) offers a useful platform for studying the metal effect on both CO2 adsorption and catalytic fixation, which is demonstrated by catalytic CO2 cycloaddition with propylene oxide to produce propylene carbonate and molecular simulations. This research sheds light on how metal exchange could influence intrinsic properties of MOFs.